MRI-based morphometric structural changes correlate with histopathology in experimental autoimmune encephalomyelitis - Lowinski, Anna; Dabringhaus, Andreas; Kraemer, Matthias; Doshi, Hardik; Weier, Alicia; Hintze, Maik; Chunder, Rittika; Kuerten, Stefanie (Journal of the Neurological Sciences, 2025)
Background and objectives Magnetic resonance imaging (MRI) and neurohistopathology are important correlates for evaluation of disease progression in multiple sclerosis (MS). Here we used experimental autoimmune encephalomyelitis (EAE) as an animal model of MS to determine the correlation between clinical EAE severity, MRI and histopathological parameters. Methods N = 11 female C57BL/6J mice were immunized with human myelin oligodendrocyte glycoprotein 1–125, while N = 9 remained non-immunized. Mice were scanned longitudinally over a period of 13 weeks using a 11.7 Tesla (T) Bruker BioSpec® preclinical MRI instrument, and regional volume changes of the lumbar spinal cord were analyzed using Voxel-Guided Morphometry (VGM). Following the final in vivo T1-weighted MRI scan, the lumbar spinal cord of each mouse was subjected to an ex vivo MRI scan using T1-, T2*- and diffusion tensor imaging (DTI)-weighted sequences. Tissue sections were then stained for immune cell infiltration, demyelination, astrogliosis, and axonal damage using hematoxylin-eosin staining and immunohistochemistry. Results While in vivo MRI VGM detected an overall increase in volume over time, no differences were observed between EAE animals and controls. Ex vivo MRI showed a generalized atrophy of the spinal cord, which was pronounced in the anterolateral tract. The most striking correlation was observed between EAE score, white matter atrophy in ex vivo T1-weighted scans and histological parameters. Discussion The data demonstrate that ex vivo MRI is a valuable tool to assess white matter atrophy in EAE, which was shown to be directly linked to the severity of EAE and spinal cord histopatholog
Keywords: Experimental autoimmune encephalomyelitis; Magnetic resonance imaging; Multiple sclerosis; T1; T2; T2*; Voxel-guided morphometry